THE RELEVANCE OF COMPOSITE BAR REINFORCEMENT IN THE FIBER FOAM CONCRETE - A. V. Visnap; V. N. Morgun; L. V. Morgun (Вестник Дагестанского государственного технического университета: Технические науки)
From the analysis of a range of energy-saving materials used in the construction, it follows that the properties of fibropenobetona allow to expand the range of products from cellular concrete. At present, therefore become topical study on the applicability of composite rod reinforcement to ensure the operational reliability of building products, working in tension and bending under the condition of reducing their consumption of materials.